Assessing the influence of fiscal and monetary policies on carbon dioxide emissions - Avinash Ramlogan; Andell Nelson (Latin American Journal of Central Banking (LAJCB), 2024)
This paper examines the impact of fiscal and monetary policies on carbon dioxide emissions in Trinidad and Tobago, using data from 1970 to 2020. We use a fiscal policy index based on government revenue and expenditure, a monetary policy index based on interest rates and reserve requirement data, and a Non-linear Autoregressive Distributed Lag technique. Our results show that expansionary fiscal policy raises emissions, while contractionary fiscal policy reduces emissions. Intriguingly, expansionary monetary policy increases emissions, while contractionary monetary policy lowers them. These findings hold significance for fiscal and monetary policymakers working on climate change mitigation strategies.
Keywords: E43; E63; E21; Q53; Q54; Q56; Q58; Q51; 330; Monetary policy; Fiscal policy; Carbon dioxide emissions; NARDL methodology; Cointegration; Energy consumption